The informal aspects of the activity of countries studied through Social Accounting and Socio-Demographic Matrices - Santos, Susana (2017)
Approaches based on Social Accounting Matrices (SAMs) and Socio-Demographic Matrices (SDMs) will be presented as a way of capturing relevant networks of linkages and the corresponding multiplier effects, which can subsequently be used for modelling the activity of the countries to be studied. Emphasis will be placed on the activity of household unincorporated enterprises, also known as informal enterprises. Based on methodological principles derived mainly from the works of Richard Stone, this study will be developed in a matrix format, including, on the one hand, people – represented by a SDM – and, on the other hand, activities, products, factors of production and institutions – represented by a SAM. The exposition will be accompanied by an application to Portugal, in which different scenarios will be briefly presented, involving changes in incomes and expenditures. The macroeconomic effects of these changes will be summarised in the form of changes in the macroeconomic aggregates: Gross Domestic Product, Gross National Income and Disposable Income.